Self-Other Asymmetry - Ogien, Ruwen (Les ateliers de l'éthique / The Ethics Forum)

(untitled) (Centre de recherche en éthique de l’Université de Montréal, 2008)
In this paper, I present a non standard objection to moral impartialism. My idea is that moral impartialism is questionable when it is committed to a principle we have reasons to reject: the principle of self-other symmetry. According to the utilitarian version of the principle, the benefits and harms to the agent are exactly as relevant to the global evaluation of the goodness of his action as the benefits and harms to any other agent. But this view sits badly with the “Harm principle” which stresses the difference between harm to others and harm to the self. According to the deontological version, we have moral duties to ourselves which are exactly symmetrical to our duties to others. But there are reasons to believe that the idea of a duty to the self is not coherent.